2007
DOI: 10.1542/peds.2006-3706
|View full text |Cite
|
Sign up to set email alerts
|

Parent Presence During Complex Invasive Procedures and Cardiopulmonary Resuscitation: A Systematic Review of the Literature

Abstract: We conducted a systematic review of the literature on parent presence during complex invasive pediatric procedures and/or resuscitation. We identified 15 studies that met our inclusion criteria. All studies were summarized chronologically according to level of evidence. The studies all demonstrated that parents prefer to have the choice about whether they remain at their child's side during complex invasive procedures and resuscitation, but they also revealed that apprehensions and controversy abound among cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 23 publications
0
69
1
3
Order By: Relevance
“…Non-pharmacological strategies should be carried out and checked every time since the admission to the unit. 1,2,[4][5][6][7] Among the non-pharmacological measures are minimization of noise in the unit -which must be as silent as possible; utilization of adequate luminosity to promote an adequate sleep-awake cycle -through less light during nighttime; promoting time to rest and sleep to maintain a circadian orientation; concentrating, as much as possible, the procedures on daytime; keeping the patient in a comfortable position, with the use of cushions, for example; stimulating the presence of companions; maintaining good communication between everyone and the medical team. The use of video-therapy and music-therapy are also procedures to promote comfort to these patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacological strategies should be carried out and checked every time since the admission to the unit. 1,2,[4][5][6][7] Among the non-pharmacological measures are minimization of noise in the unit -which must be as silent as possible; utilization of adequate luminosity to promote an adequate sleep-awake cycle -through less light during nighttime; promoting time to rest and sleep to maintain a circadian orientation; concentrating, as much as possible, the procedures on daytime; keeping the patient in a comfortable position, with the use of cushions, for example; stimulating the presence of companions; maintaining good communication between everyone and the medical team. The use of video-therapy and music-therapy are also procedures to promote comfort to these patients.…”
Section: Resultsmentioning
confidence: 99%
“…The use of video-therapy and music-therapy are also procedures to promote comfort to these patients. 1,2,[4][5][6][7] Management of pain/sedation The International Association for the Study of Pain defines pain as a sensorial and emotional, unpleasant experience, associated with an actual or potential lesion to tissues. In the ICU, we can distinguish between two types of pain: (1) acute pain, including procedure and post-operative pain; and (2) prolonged pain -which is pain caused by a disease (like peritonitis, mechanical ventilation, tubes and drains etc.…”
Section: Resultsmentioning
confidence: 99%
“…The American Heart Association reported in its guideline that children may be accompanied by their parents during invasive procedures and/or resuscitations (13), because the parents' presence would not only make a contribution to the patients' recovery but also help calm down both the families and the children (14). A study indicated that although there was no decrease in pain scores in the cases where parents accompanied their children during painful invasive procedures, such as intravenous access procedure, there was an increase in the satisfaction level of both patients and parents (15).…”
Section: Discussionmentioning
confidence: 99%
“…Funnene indikerer at foreldrene stort sett får vaere til stede hos sine barn, men at de opplever enkeltepisoder hvor de ikke får vaere til stede hos barnet, under rapport og i akuttsituasjoner. Det synes å vaere stor enighet i forskningen om at foreldre skal vaere til stede så mye de ønsker, selv under krevende akuttsituasjoner (31)(32)(33). Foreldre som får vaere til stede under kritiske situasjoner vil oppleve mindre redsel og angst.…”
Section: Diskusjonunclassified